A Prospective, Up-down Sequential Allocation Study Investigating the Effectiveness of Vital Capacity Breaths Using High-flow Nasal Oxygenation versus a Tight-fitting Face Mask to Preoxygenate Term Pregnant Women. Issue 4 (December 2021) - Al-Sulttan, S.; Bampoe, S.; Howle, R.; Setty, T.; Columb, M.; Patel, A.; Fernando, R.; Husain, T.; Sultan, P.
Abstract : ( Int J Obstet Anesth . 2021;45:28–33) While neuraxial anesthesia is the preferred technique for cesarean delivery (CD), sometimes general anesthesia (GA) is warranted. Preoxygenation before rapid-sequence induction of GA in obstetric patients can prolong the time to oxygen desaturation. High-flow nasal oxygenation (HFNO) has been used in other settings, but there is a lack of data on its use in the obstetric population. A previous study examined the use of HFNO, using tidal volume breaths rather than vital capacity (VC) breaths. This current study aimed to determine the number of VC breaths needed using HFNO to achieve FET O2 ≥90% in pregnant women undergoing CD at term, and compare this to the number of VC breaths needed to achieve FET O2 ≥90% using a tight-fitting face mask for preoxygenation.